1987
DOI: 10.3382/ps.0661957
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Nitrate and Nitrite in Raw Turkey Breast Meat and the Microbial Conversion of Added Nitrate to Nitrite in Tumbled Turkey Breast Meat

Abstract: The concentrations of nitrate and nitrite in raw turkey breast meat and the microbial conversion of nitrate to nitrite in an uncured tumbled breast meat product were studied to assess their involvement in the formation of undesirable pinkness. Nitrate concentration in raw turkey breast meat ranged from 3.8 to 21 ppm and nitrite varied from 0 to .7 ppm. Microorganisms in the tumbled meat sample converted the nitrate to nitrite; 5.2 ppm of nitrite (NaN0 2 ) were formed from 100 ppm of added nitrate (KN0 3 ) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…Ahn and Maurer (1987) reported that the residual nitrite contents of 0.2 ppm were naturally present in raw turkey breasts, which is similar to our result.…”
Section: Resultssupporting
confidence: 92%
“…Ahn and Maurer (1987) reported that the residual nitrite contents of 0.2 ppm were naturally present in raw turkey breasts, which is similar to our result.…”
Section: Resultssupporting
confidence: 92%
“…Sample preparation and nitrate determination methods were modifications of Ahn and Maurer (1987). Five grams of meat product samples were weighed in a 50‐mL test tube and homogenized with 20 mL of DDW using a Polytron homogenizer (Type PT 10/35, Brinkmann Instruments Inc., Westbury, N.Y., U.S.A.) for 10 s at high speed.…”
Section: Methodsmentioning
confidence: 99%
“…Residual nitrate was determined using high pressure liquid chromatography (Witter & Balish, 1979;Witter, Gatley, & Balish, 1982) with modifications as described by Ahn and Maurer (1987). Samples were prepared in duplicate and evaluated on days 0, 4 and 10 for C. perfringens samples and days 0, 14, and 35 for L. monocytogenes samples.…”
Section: Residual Nitratementioning
confidence: 99%